Cerita Rakyat Silancang dan Dampo Awang: Sebuah Kajian Bandingan: Folklore Silancang and Dampo Awang a Comparative Study - Mochammad Fikri (Balai Bahasa Provinsi Papua, 2019)
Indonesia has extraordinary cultural wealth. Folklore is one of the national cultural assets owned by Indonesian people. Some folklore has similarities and differences. For example, Silancang folklore from Sumatra Island, Riau precisely with Dampu Awang which owned by Rembang, Central Java. Both of these folklore are interesting to study because as far as researchers know there is no comparative study. This study, analyze the similarities and differences of the intrinsic elements contained in both folklore. This research is explanatory. The technique that used to collecting the data is literature study. The method that used in this research is descriptive comparative analysis method. The approach used is a discursive approach. The results of the study show that there are similarities and differences in the intrinsic elements of Silancang and Dampo Awang folklore. The similarities appear in the elements of theme, plot, character and characterization, and setting.